Salinity tolerance of the larvae of mud crab Scylla olivacea (Crustacea Portunidae). - Jusdin, Rovel John V.
The salinity tolerance of the larvae of the commercially important species of mud crab, Scylla olivacea was investigated. This study aimed to find out the optimum salinity range that could be tolerated by the different larval stages. Survival and metamorphosis of each of the five zoeal stages (Z1, Z2, Z3, Z4, Z5) and megalopa Scylla olivacea hatched and reared at 34 ppt and abruptly transferred to different salinities were determined. The different salinity levels tested for zoeal stages were 15, 20, 25, 30, 35, 40 and 45 ppt. For megalopa, additional lower salinities of 5 and 10 ppt were tested. Thirty zoea larvae were used in every replicate, and ten larvae in megalopa experiment. Another set-up was prepared where larvae were gradually transferred to low salinity of 15 ppt and to a high level of 45 ppt from respective ambient rearing salinity. In all of these salinity levels, survival and development of the larvae were monitored daily. The experiment was terminated when more than 50 of the larvae have already developed to the next larval stage. Results showed that Z1,Z2,Z3, and Z4 larvae survived and molted at a salinity range of 20-40 but optimum was at 25-35 ppt, while Z5 preferred a 20-30 ppt range. There was high megalopa survival and development at a range of 20-25 ppt. Zoea and megalopa stages did not survive at extreme salinities of 15 and 45 ppt. For the larvae that were gradually transferred and maintained at extreme salinities of 15 and 45 ppt, there was high survival but larvae failed to develop to the next larval stage on the duration of culture days observed.